STRATEGI KOMUNIKASI HUMAS DALAM MEMPERBAIKI CITRA KEMENTERIAN PEMUDA DAN OLAHRAGA REPUBLIK INDONESIA - EKO MARYADI (JURNAL EKONOMI, SOSIAL & HUMANIORA, 2020)
The arrest operation (OTT) of the Corruption Eradication Commission against Kemenpora officials at the end of 2018 which then made government institutions back into the public spotlight. Corruption cases are always in the spotlight of the community. This case makes the Ministry of Youth and Sports through public relations must make appropriate strategies so that the image of this institution does not deteriorate or even be improved. This study discusses the strategies used by Kemenpora public relations in discussing public trust. This research uses a qualitative method by collecting data through documentation studies. This research is expected to be able to discuss other institutions that might discuss the same problem.